تحليل المستوى المعرفي للتمرينات في كتاب مختارات قواعد اللغة العربية بناء على تصنيف بلوم - Alianto Alianto; Nur Cholis Agus Santoso (Lembaga Yasin AlSys, 2026)
Although the analysis of exercises in Arabic language textbooks has received attention in several previous studies, research specifically examining the exercises in the book Mukhtarat Qawa’id al-Lughah al-‘Arabiyyah remains limited. This study aims to analyze the exercises in the book and identify their cognitive levels based on the revised Bloom’s Taxonomy. This study used a qualitative approach with a content analysis design, involving all exercises in the nahwu and sharaf sections, totaling 103 exercises. Data were collected through an analytical instrument based on operational verbs referring to cognitive levels and were analyzed using quantitative descriptive techniques through frequency and percentage calculations. The results showed that the exercises were dominated by low to moderate cognitive levels. The levels of remembering (C1) and understanding (C2) occupied the highest positions, each with a percentage of 34%, followed by applying (C3) at 19% and analyzing (C4) at 13%. Meanwhile, the levels of evaluating (C5) and creating (C6) were not found. In addition, the sharaf section only covered the levels of understanding and applying, whereas the nahwu section covered four cognitive levels. These findings contribute to the development of Bloom’s Taxonomy theory in the context of Arabic language learning and broaden understanding of the characteristics of exercises in textbooks. The conclusion of this study emphasizes the importance of developing exercises that include higher-order thinking skills. Therefore, the authors suggest that curriculum developers and educators design more varied exercises, including those at the levels of analysis, evaluation, and creation. The implications of this study include a theoretical contribution to enriching content analysis studies of Arabic language textbooks, as well as practical implications for educational institutions in improving the quality of learning. This study also opens opportunities for further research that examines the effect of exercises on language proficiency in a more applied manner.